5037 Coronary artery disease risk assessment by coronary artery calcium scoring in asymptomatic Thai people with diabetes mellitus - Thewjitcharoen, Yotsapon; Chatchomchaun, Waralee; Nakasatien, Soontaree; Butadej, Siriwan; Wanothayaroj, Ekgaluck; Krittiyawong, Sirinate; Himathongkam, Thep (Journal of the Endocrine Society, 2024)
Abstract Disclosure: Y. Thewjitcharoen: None. W. Chatchomchaun: None. S. Nakasatien: None. S. Butadej: None. E. Wanothayaroj: None. S. Krittiyawong: None. T. Himathongkam: None. Background: Despite major advances in treatment, people with diabetes mellitus (DM) remain at high risk of cardiovascular (CV) disease. The use of CV risk assessment in individuals with DM with coronary artery calcium (CAC) has been controversial and is not recommended by current guidelines. However, CAC has been demonstrated as the most powerful CV risk indicator in the asymptomatic population, with consistent superiority to all clinical risk factor-based algorithms. Moreover, the CAC score is also an independent marker of risk for cardiac mortality, and all-cause mortality. Objectives : This study aimed to evaluate the severity and correlation of CAC in asymptomatic Thai people with DM, and impacts on patient managements. Methods: This retrospective cohort study included asymptomatic Thai people with DM who underwent CAC measurement between January 2020 and December 2022 at Theptarin Hospital, Bangkok, Thailand. Four CV risk scores (Thai CV risk score, ASCVD risk score, SCORE2 model, and UKPDS risk score) were applied and the estimated risk scores were correlated with the severity of CAC. ABC control, defined as the proportion of individuals who jointly met glycemic, blood pressure, and LDL cholesterol targets at 6 months after the CAC measurement. Results: A total of 157 patients (female 45.2%, T2D 93.0%, mean age 61.7±13.3 years, mean DM duration 12.4±10.6 years, BMI 26.4±4.8 kg/m2, A1C 7.4±1.9%, insulin usage 28.7%) were included in the study. Zero calcium score was found in 24.2% and CAC score ≥ 100 AU was found in 40.3% of all patients. Spearman correlation coefficients for the presence or absence of CAC with various CV scores classified as low-risk ranged from 0.374 to 0.472. There was a weak to moderate significant positive correlation between different CV risk scores with the presence of CAC score ≥ 100 AU. In those with CAC score ≥ 100 AU, aggressive lipid-lowering therapy (statin intensification or adding ezetimibe), new prescription of SGLT2i or GLP-1 RA, new prescription of antiplatelet (aspirin or clopidogrel) as primary prevention were all increased when compared with CAC < 100 AU. At 6 months, subjects who met ABC target increased from 30.4% to 55.7% in those with CAC ≥ 100 AU in comparison to the increment of 35.9% to 56.4% in patients those with CAC < 100 AU. Conclusions: CAC is a useful tool for CV risk stratification among asymptomatic people with DM and could influence metabolic target attainment rates. Our study also illustrated the impact of CAC scoring on prescribing practices. Currently available risk assessment models including diabetes-specific risk scores tend to overestimate the CV risk in Thai people with DM. Presentation: 6/3/2024